Strategi Pengembangan Usahatani Jahe (Zingiber Officinale) Di Kecamatan Jenawi Kabupaten Karanganyar - Novianto, Andi; Dewati, Rosita (Journal of Agribusiness, Social and Economic, 2021)
prospect of developing ginger farming in Jenawi District has great potential because the ginger cultivated is of good quality. The type of ginger that is widely cultivated in Jenawi District is emprit ginger, emprit ginger has a strong spicy taste and a lot of essence. The purpose of this research is to determine the right strategic priority for developing ginger farming in Jenawi District. This research was conducted in ginger farming, Jenawi District, Karanganyar Regency. The basic method used is descriptive analytical. The types of data used are primary data and secondary data. The data analysis method used is farm analysis. The strategy formulation at the input stage uses the IFE matrix and the EFE matrix, at the matching stage using the SWOT matrix, and at the decision stage using the QSPM matrix. The results showed that the total cost was Rp. 34,417,711 / Ha, revenue Rp. 153,986,333 / Ha, income of IDR 119,568,622 / Ha. From the IFE matrix identified 4 strengths, 4 weaknesses, and the EFE matrix 4 threats, 5 threats. From the SWOT matrix, it produces 6 alternative strategies. The QSPM matrix produces strategic priorities, which is to collaborate with the Department of Agriculture to hold counseling and comparative studies so as to increase the knowledge and managerial skills of farmers so that they can improve ginger farming effectively and efficiently, because they get a total TAS value of 5.72.